Development of a high-performance liquid chromatography method based on a core-shell column approach for the rapid determination of multiclass polyphenols in grape pomaces - Fontana, Ariel Ramón (2015)
A rapid and economically affordable reverse-phase chromatographic approach based on a core-shell column with high-performance liquid chromatography multi-wavelength detector (HPLC-MWD) is proposed for the quantification and quality control of multiclass polyphenols (PPs). The separation of 20 relevant polyphenols from grape pomace extracts (GPEs) was achieved in less than 12 min by using a Kinetex C18 column (3.0 mm x 100 mm, 2.6 µm) with a gradient system of ultrapure water (0.1 % formic acid) and acetonitrile, a temperature of 35 °C and a flow rate of 0.8 mL min-1. The maximum backpressure reached was 327 bar, meaning the developed method is adequate for standard HPLC instruments. The applicability of the method was demonstrated by the determination of PPs in GPEs of different red grape varieties. Cabernet Sauvignon GPE showed the highest content of studied PPs (9804.2 µg g-1 GPE) followed by Bonarda GPE (7302.0 µg g-1 GPE). Besides the methodological development for a high throughput routine quality control of GPEs, this is the first report of PPs content for Bonarda and Aspirant Bouchet GPE, so the results add knowledge for these grape varieties cultivated in Argentina.